Sugarcane bagasse as a potential functional ingredient in noodles with nutritional, functional and sensorial acceptability - Lau, Ke Qi (2022)
Sugarcane bagasse (SB) is one of the most abundant food wastes, mainly originating from the sugar industry, as up to 85% of SB are used as burning material. SB was reported to contain high dietary fibre and low glycemic index, which could be a potential functional ingredient. In this research, SB was incorporated into the development of noodles at three different ratios which were 5%, 10% and 15%, and noodle made without the addition of SB was used as control. In addition, a commercial noodle with similar ingredients was also used to compare with the SB incorporated noodle samples. Physical properties, proximate composition and mineral content, antioxidant properties, functional properties, dialyzable glucose and sensory score of noodles were tested to determine the suitability of SB incorporation. In terms of physical properties, 10% and 15% sugarcane bagasse incorporated noodles (SBN) had significantly (p<0.05) higher score of darkness and cohesiveness as compared to control sample. The antioxidant properties of SB noodles were significantly (p<0.05) increased up to 770% in DPPH assay and 244% in total phenolic compounds with 15% SB incorporation. Noodle sample with 5% SB incorporation showed the closest value with commercial noodle in terms of the functional properties. There is no significant difference in terms of water absorption index and sweeling index between 5% SBN with commercial and control noodles. Total dietary fibre of noodles was significantly (p<0.05) increased from 3.39% (control) to 13.85% when incorporating 15% SB. All three SBNs i.e 5, 10 and 15% noodles were qualified to be labelled as “High in dietary fibre”. Sensory evaluation was also carried out to estimate the consumers’ preference towards the SBN. Noodle with 5% SB incorporation had the highest overall acceptability as compared to 10% and 15% noodle and the difference was statistically significant (p<0.05). As such, noodle sample with 5% SB incorporation was found to be the most suitable ratio in noodle development. In addition, noodle sample with 5% SB incorporation showed the closest value towards commercial noodles in terms of colour, texture and functional properties, with high fibre content and antioxidant activity as well as a decent and acceptable level of overall sensory acceptability.